A differential game model for emission reduction decisions between ports and shipping enterprises considering environmental regulations. (15th June 2022) - Meng, Lingpeng; Wang, Jingmei; Yan, Wei; Han, Chuanfeng
Abstract: Ports and shipping enterprises are important subjects of carbon emissions in terms of achieving carbon peak and neutrality goals. A differential game model is proposed to explore the impact of government regulations on the cooperation between ports and shipping enterprises to reduce emissions. The model is constructed for four scenarios based on incentive subjects and decision-making methods. The results of the model are as follows. (1) Government incentives for both ports and shipping enterprises can increase the emission reduction efforts of both parties, with the benefits for shipping enterprises being greater than those for ports in the four models. (2) When the government provides incentives only to the port, if the port subsidizes shipping enterprises and the decision is decentralized between them, then the emission reduction is expected to be the best, but it is unfavorable for the port's revenue. If a benefit-sharing mechanism is introduced to centralize the decision, then the emission reduction effect is better in the initial stage and the port's revenue increases, but in the long run, the port is still in a low-emission-reduction state. The emission reduction effect is not satisfactory if the port and shipping enterprises subsidize each other, although doing so increases the port's revenue. Although this strategy increases port revenue, it largely reduces the interests of shipping enterprises. Therefore, emission reductions are better when the government sets queues for ports and shipping enterprises, but subsidy factor settings need to be considered to improve port yields.